2011
DOI: 10.1073/pnas.1105880108
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of the enhanced aromatic sequon is similarly stabilizing in three distinct reverse turn contexts

Abstract: Cotranslational N-glycosylation can accelerate protein folding, slow protein unfolding, and increase protein stability, but the molecular basis for these energetic effects is incompletely understood. N-glycosylation of proteins at naïve sites could be a useful strategy for stabilizing proteins in therapeutic and research applications, but without engineering guidelines, often results in unpredictable changes to protein energetics. We recently introduced the enhanced aromatic sequon as a family of portable stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(153 citation statements)
references
References 60 publications
3
148
0
2
Order By: Relevance
“…Indeed, molecular dynamics analyses on our model protein had suggested a direct interaction of the glycan with surrounding amino acids (16) and recent studies characterized the CH-p interaction between the CH groups of the first GlcNAc of the glycan core and aromatic amino acid side chains of the glycoproteins (46). The presence of phenylalanine at the 22 position of the N-glycosylation sequon localized in a reverse turn increases the stability of the protein, but also of glycan homogeneity (47)(48)(49). We thus hypothesized that, in PDI, the glycan structures observed on site 4 are the result of the change in the glycan torsion caused by the interaction of the core GlcNAc with the tyrosine, itself favoring the interaction of the whole glycan with the protein surface and the domain a of PDI.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, molecular dynamics analyses on our model protein had suggested a direct interaction of the glycan with surrounding amino acids (16) and recent studies characterized the CH-p interaction between the CH groups of the first GlcNAc of the glycan core and aromatic amino acid side chains of the glycoproteins (46). The presence of phenylalanine at the 22 position of the N-glycosylation sequon localized in a reverse turn increases the stability of the protein, but also of glycan homogeneity (47)(48)(49). We thus hypothesized that, in PDI, the glycan structures observed on site 4 are the result of the change in the glycan torsion caused by the interaction of the core GlcNAc with the tyrosine, itself favoring the interaction of the whole glycan with the protein surface and the domain a of PDI.…”
Section: Discussionmentioning
confidence: 99%
“…Protein glycosylation is either N-linked (GlcNAcβ-Asn) linkage with a minimal amino acid sequence of Asn-X-Ser/Thr, (where X ≠ Pro) or O-linked (where GalNAc is added to Ser or Thr), and GSLs are synthesized by a sequential transfer of sugar residues to a ceramide lipid anchor. Interestingly, all share pivotal roles such as cellular differentiation, adhesion, immunity, signal transduction and growth control [16][17][18]. However, there is no comprehensive glycomics focusing on mammalian brain glycoconjugates towards the discovery of neurodegenerative biomarkers while a few N-and O-glycans specific to rat brain glycoproteins have been reported [19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Glycosylated rCel5A showed higher thermal stability than deglycosylated rN124D. The result is expected because many previous studies showed that the increased levels of glycosylation could improve the thermotolerance of glycoproteins (31-33). Although N124 was located outside the (α/β) 8 barrel, the covalent binding of glycans to the protein surface may inherently enhance the thermal and kinetic stabilities of proteins.…”
Section: Discussionmentioning
confidence: 87%